ANALISIS TIPE KEPRIBADIAN DENGAN KEJADIAN HIPERTENSI - Khotimah; Mustofa, Andika Sri Kresno Eko (Journal of Pubnursing Sciences, 2026)
Hypertension is a chronic condition that is often referred to as a silent killer because it shows no symptoms until serious complications such as stroke or heart disease occur. Risk factors for hypertension include age, lifestyle, obesity, and psychological aspects such as personality type. Type A personalities who tend to be ambitious, competitive and prone to stress are associated with increased blood pressure, while Type B personalities are more relaxed and have a lower risk. This study aimed to understand the relationship between personality type and the incidence of hypertension in Kunjang Health Center. This study used a case-control design. The population of this study were hypertensive patients at the Kunjang Health Center who had been sampled using simple random sampling technique, resulting in 38 respondents who were divided into hypertensive and non-hypertensive groups. Data collection instruments were carried out through blood pressure measurements using a digital sphygmomanometer and a personality type questionnaire. After that, testing was carried out with the Chi-Square test. The results of bivariate analysis showed a significance value of 0.00, which means there is an association between personality type and the incidence of hypertension. Individuals with Type A personality have a higher risk than Type B personality. Higher stress in Type A personality can increase adrenaline and cortisol hormones, which have an impact on increasing blood pressure. Therefore, health education on stress management and the implementation of a healthy lifestyle are needed to prevent and control hypertension.